Evaluating the Outcomes of Rotator Cuff Repairs With Polytetrafluoroethylene Patches for Massive and Irreparable Rotator Cuff Tears With a Minimum 2-Year Follow-up. Issue 13 (November 2018) - Seker, Vasanth; Hackett, Lisa; Lam, Patrick H.; Murrell, George A.C.
Background: Massive and irreparable rotator cuff tears are difficult to manage surgically. One technique is to use a synthetic polytetrafluoroethylene (PTFE) patch to bridge the tear. However, there is little information regarding the outcomes of this procedure. Purpose: To determine the ≥2-year outcomes of patients for whom synthetic patches were used as tendon substitutes to bridge irreparable rotator cuff defects. Study Design: Case series; Level of evidence, 4. Methods: This retrospective cohort study used prospectively collected data. Patients included those with a synthetic patch inserted as an interposition graft for large and/or irreparable rotator cuff tears with a minimum 2-year follow-up. Standardized assessment of shoulder pain, function, range of motion, and strength was performed preoperatively, at 6 and 12 weeks, and at 6 months and ≥2 years. Radiograph and ultrasound were performed preoperatively, at 6 months, and ≥2 years. Results: At a mean of 36 months, 58 of 68 eligible patients were followed up, and 53 of 58 (90%) patches remained in situ. Three patches failed at the patch-tendon interface, while 1 patient (2 shoulders/patches) went on to have reverse total shoulder replacements. Patient-ranked shoulder stiffness ( P < .001), frequency of pain with activity and sleep ( P < .0001), level of pain at rest and overhead ( P < .0001), and overall shoulder function improved from bad to very good ( P < .0001) by 6 months. Supraspinatus (mean ± SEM: 29 ± 16 N to 42 ± 13 N) and external rotation (39 ± 13 N to 59 ± 15 N) strength were the most notable increases at the ≥2-year follow-up ( P < .0001). Passive range of motion also improved by 49% to 67%; forward flexion, from 131° to 171°; abduction, from 117° to 161°; external rotation, from 38° to 55°; and internal rotation, from L3 to T10 ( P < .0001) preoperatively to ≥2 years. The most improvement in passive range of motion occurred between 12 months and ≥2 years. The mean (SD) Constant-Murley score was 90 (12), while the American Shoulder and Elbow Surgeons score was 95 (8). Conclusion: At 36 months postoperatively, patients who had synthetic patches used as tendon substitutes to bridge irreparable rotator cuff defects reported less pain and greater overall shoulder function as compared with preoperative assessments. They demonstrated improved range of passive motion and improved strength. The data support the hypothesis that the technique of using a synthetic PTFE patch to bridge a large and/or irreparable tear has good construct integrity and improves patient and clinical outcomes.